A possible deforestation-induced synoptic-scale circulation that delays the rainy season onset in Amazonia. (1st April 2023) - Commar, Luiz Felipe Sant'Anna; Abrahão, Gabriel Medeiros; Costa, Marcos Heil
Abstract: The physical hydroclimate system of the Amazon functions on several spatial and temporal scales. Large-scale processes control the main seasonal patterns of atmospheric circulation and rainfall. Seasonal variability in solar forcing, associated with the low rainforest albedo, provides energy for continental heating, convection, and the onset of the South American monsoon. Mesoscale processes cause localized circulations such as river breeze and deforestation breeze. We assessed the impact of different deforestation scenarios for the mid-century last decade rainy season. Here we describe a yet unreported synoptic-scale circulation that delays the rainy season onset in southern Amazonia. This model-predicted circulation is driven by extensive (ca. 40%) deforestation patterns and may last as long as two months. This persistent anomalous circulation may result in a rainy season onset delay of 30–40 d compared to the historical period. Like other synoptic-scale phenomena, differences in surface heating drive this circulation. Given the unabated deforestation trends, the consequences for local ecosystems, agriculture, and power generation of delayed rainy season onset associated with this circulation may be difficult to revert.